(untitled) (Global Journal of Medical Research, 2013)
A novel elicitor (PiPE) from the oomycete Phytophthora infestans (Pi) stimulates the hypersensitive response (HR) in potato. The PiPE, purified by anion-exchange chromatography from a water-soluble extract of Pi caused cell death, characteristic of HR, and enhanced active oxygen species (AOS) generation in tuber tissues. The partial amino acid sequence, and the sequence of the PiPE cDNA derived by PCR had homologous domain to fructose 1,6 bisphosphate aldolase (FBA) genes. To demonstrate that the PiPE cDNA encodes an active elicitor, we expressed PiPE in Echerichia coli, high five insect cells and purified the recombinant protein. His-PiPE induced HR, browning and generation of AOS in potato tissues. The PiPE was produced in the germination fluid from Pi and was existing in the cell wall of Pi. The role of PiPE peptides in the induction of HR in an incompatible interaction between Pi and potato cells is a prerequisite for the AOS and HR induction.